Edukasi Pentingnya Perilaku Aman dalam Menjaga Keselamatan Nelayan - Astrid Pratiwi Rufaedah Amir; Jumhur Salam; Khafifa S (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Fishermen are one of the worker groups with high occupational risks due to extreme weather, the use of traditional equipment, and the lack of safety standard implementation. Kampung Beru Village, located in Galesong District, Takalar Subdistrict, is a newly established village in 2022, where most of the population works as fishermen. Most fishermen admit that they have not yet implemented proper and appropriate safety management in their fishing activities. This is due to their limited knowledge of work safety standards. This habit is certainly very risky, considering the many potential dangers that can occur at sea. Therefore, this community service activity aims to provide education on the importance of safe behavior in ensuring fishermen’s safety through lectures and direct socialization. The results of this activity show an increase in the fishermen's understanding in Kampung Beru Village regarding the importance of applying safe behavior for their own safety.)